Intelligent design uncensored: an easy-to-understand guide to the controversy - Dembski, William A. (IVP Books, 2010)
Fantastic voyage -- The design revolution -- The world's smallest rotary engine -- The design test -- The poison of materialism -- Breaking the spell of materialism -- The book of nature: lifting the ban